Elevated pulmonary tuberculosis biomarker miR-423-5p plays critical role in the occurrence of active TB by inhibiting autophagosome-lysosome fusion. Issue 1 (1st January 2019) - Tu, Huihui; Yang, Su; Jiang, Tingting; Wei, Liliang; Shi, Liying; Liu, Changming; Wang, Chong; Huang, Huai; Hu, Yuting; Chen, Zhongliang; Chen, Jing; Li, Zhongjie; et al.
ABSTRACT: Rapid diagnosis of pulmonary tuberculosis is an effective measure to prevent the spread of tuberculosis. However, the grim fact is that the new, rapid, and safe methods for clinical diagnosis are lacking. Moreover, although auto-lysosome is critical in clearing Mycobacterium tuberculosis, the pathological signiﬁcance of microRNAs, as biomarkers of tuberculosis, in autophagosome maturation is unclear. Here, these microRNAs were investigated by Solexa sequencing and qPCR validation, and a potential diagnostic model was established by logistic regression. Besides that, the mechanism of one of the microRNAs involved in the occurrence of tuberculosis was studied. The results showed that the expression of miR-423-5p, miR-17-5p, and miR-20b-5p were signiﬁcantly increased in the serum of patients with tuberculosis. The combination of these three microRNAs established a model to diagnose tuberculosis with an accuracy of 78.18%, and an area under the curve value of 0.908. Bioinformatics analysis unveiled miR-423-5p as the most likely candidate in regulating autophagosome maturation. The up-regulation of miR-423-5p could inhibit autophagosome maturation through suppressing autophagosome–lysosome fusion in macrophages. Further investigations showed that VPS33A was the direct target of miR-423-5p, and the two CUGCCCCUC domains in VPS33A 3'-UTR were the direct regulatory sites for miR-423-5p. In addition, an inverse correlation between VPS33A and miR-423-5p was found in peripheral blood mononuclear cells of patients with tuberculosis. Since the inhibition of autolysosome formation plays a critical role in tuberculosis occurrence, our ﬁndings suggests that miR-423-5p could suppress autophagosome–lysosome fusion by post-transcriptional regulation of VPS33A, which might be important for the occurrence of active tuberculosis.